Moth monitoring in Northeastern Iceland - Kolbeinsson, Yann; Kolbeinsson, Yann (Polar Data Catalogue, 2015)
The goal is to monitor the distribution and population dynamics of moths in Iceland in relation with abiotic environmental factors. Moths are collected in light-trap annually from week 16 to week 40. Abiotic factors are monitored at fixed weather stations in the area by the Icelandic Meteorological Office.